Association of a novel nutritional marker, the triglyceride-cholesterol-body weight index, with 90-day unfavorable outcomes in acute ischemic stroke: a prospective cohort study - Xiao, Binhui; Zhu, Jiaqian; Han, Yong (Frontiers in Nutrition, 2026)
ObjectiveCurrently, research on the relationship between triglyceride-total cholesterol-body weight index (TCBI) and prognosis in patients with Acute Ischemic Stroke (AIS) is relatively limited. Therefore, this study aims to investigate the association between TCBI and the incidence of unfavorable functional outcomes in AIS patients.MethodsThis secondary analysis included 1,764 AIS patients admitted to a South Korean hospital from January 2010 to December 2016. Binary logistic regression assessed the association between TCBI and 90-day unfavorable outcomes (defined as mRS score ≥3). A logistic regression model with restricted cubic spline functions was employed to explore the potential nonlinear relationship between them. A series of sensitivity analyses (including analyses restricted to participants without DM, without smoking, or with BMI < 28 kg/m2, as well as analyses using generalized additive models and E-value calculations) and subgroup assessments were conducted to further validate the robustness of the findings.ResultsAfter adjusting for confounders, TCBI (per 100-unit increment) was inversely associated with 90-day unfavorable outcomes (OR = 0.972, 95% CI: 0.953–0.991). A nonlinear relationship was identified with an inflection point at TCBI = 1227.3. Below this inflection point, every 100-unit increment in TCBI demonstrated an OR of 0.928 (95% CI: 0.8866–0.9714) for unfavorable outcomes at 90 days. Above this turning point, the corresponding OR was 0.983 (95% CI: 0.955–1.287). Sensitivity analyses showed that the OR (95% CI) for the association between TCBI (per 100-unit) and 90-day unfavorable outcomes were 0.969 (0.944–0.993), 0.971 (0.946–0.996), and 0.972 (0.952–0.992) in participants without DM, without smoking, and with BMI < 28 kg/m2, respectively. No significant interactions were observed in subgroup analyses stratified by age, sex, previous stroke/TIA, hypertension, CHD, stroke etiology, or AF (all P for interaction ≥0.05).ConclusionThis study revealed an independent negative link between TCBI and unfavorable outcomes at 90 days in patients with AIS. A nonlinear relationship between them was observed. When TCBI values were below 1227.3, a significant negative correlation was found. This provides new insights for prognostic stratification, optimization of rehabilitation strategies, and clinical management in AIS patients.